A HISTOLOGICAL STUDY ON THE EFFECT OF AQUEOUS EXTRACT OF Capsicum spp. ON Entamoeba histolytica IN ALBINO MICE. - Mahmood, Suhaila; Mohamed, Ban (Iraqi Journal of Science, 2024)
The present study was conducted to determine the effect of hot pepper Capsicum spp. on the cysts and trophozoites stages of Entamoeba histolytica in albino mice. The previosly infected mice with E. histolytica were administered with two doses (0.01 and 0.03 ml) of aqueous extract of hot pepper three times daily at(morning, afternoon and evening) for a period of 7 days. The results showed that the aqueous extract of hot pepper was very effective in decreasing the numbers of cysts and trophozoites of E. histolytica in mice. The highest percentage was recorded with the dose of 0.03 ml which was100 % for trophozoites and 90.1 % for cysts. The histological study of small and large intestine and liver revealed that the low concentration was more effective to eliminate the injuries in small and large intestine and liver.